The Deception of Art : Analisis Potensi Ancaman NFTs (Non-Fungible Tokens) Terhadap Keamanan Nasional Indonesia - Yosafat Caesar Sinurat; Ika Riswanti Putranti; Marten Hanura (Journal of International Relations, 2022)
Technological developments have brought world civilization to a time where everything relies heavily on technology. This development greatly affects all aspects of human life. We can see this from the daily life of humans who are very dependent on the digital world and the internet. The use of the digital world can be seen in vital aspects such as the world of banking, transactions, even in the creative industry. The use of NFT as a way for creative industry activists is a new way to gain and appreciate the work they produce. Aspects that are affected, not only make it easier for humans to do work, but the development of this technology is also used as a gap by criminals to commit crimes. Money laundering crimes and terrorism financing are no longer carried out conventionally, but have penetrated into the digital world. This study aims to find loopholes in the use of NFT as a medium in committing money laundering and terrorism financing crimes, and why it can become a national threat if there is no securitization of the issue. This study uses constructivism theory with the concept of securitization. This study also found that the anonymity feature in NFT transactions can make it easier for criminals to commit money laundering and terrorism financing crimes that can threaten the national security of a country.